New technology adoption at Toolmatch Sdn. Bhd. - Abd Rahman, Azmawani; Senik, Rosmila (Universiti Putra Malaysia Press, 2010)
This case illustrates the experience of a company, Toolmatch Sdn. Bhd. in adopting a robotic welding system. The technology was adopted to enable the company to deliver quality product in a fast and reliable manner. This case provides information about what could go wrong in the process of new technology implementation especially to the novice users, who are lacking of knowledge and skills on the technology and its implementation process. Complications and problems faced by Toolmatch during the process of technology implementation are highlighted in the case. This case presents opportunities to discuss technology adoption process and application of a system development model and to evaluate and discuss the key success factors of new technology adoption. If the technology is managed effectively, expensive mistakes may be avoided.